Use of objective neurocognitive measures to assess the psychological states that influence return to sport following injury - Schilaty, N. D.; Nagelli, C.; Hewett, T. E. (Sports Medicine, 2016)
There is growing interest in the effects of psychological states on human performance, especially with those who have suffered debilitating injury and are attempting to return to sport (RTS). Current research methods measure psychological states through validated questionnaires; however, these outcomes only allow for subjective assessment and may be unintentionally biased. Application of objective neurocognitive measures correlated with psychological states will advance understanding of injury outcomes by identifying human behavior and avoiding vague assumptions from subjective measures.